Combination of TLR2 and TLR3 agonists derepress infectious bursal disease virus vaccine-induced immunosuppression in the chicken - Bashir, Khalid (Sci Rep, 2019)
Live intermediate plus infectious bursal disease virus (IBDV) vaccines (hot vaccines) are used for protection against the virulent IBDV strains in young chickens. We evaluated the potential of Toll-like receptor (TLR) agonists to alleviate hot vaccine-induced immunosuppression. The combination of Pam3CSK4 and poly I:C synergistically upregulated IFN-β, IFN-γ, IL-12, IL-4, and IL-13 transcripts and cross-inhibited IL-1β, IL-10, and iNOS transcripts in the chicken peripheral blood mononuclear cells (PBMCs) as analyzed by quantitative real-time PCR. Further, four-week old specific pathogen free White Leghorn chickens (n = 60) were randomly divided into six groups and either immunized with hot IBDV vaccine with or without Pam3CSK4 and/or poly I:C or not vaccinated to serve as controls. The results indicated that poly I:C alone and in combination with Pam3CSK4 alleviated vaccine-induced immunosuppression, as evidenced by greater weight gain, increased overall antibody responses to both sheep erythrocytes and live infectious bronchitis virus vaccine, upregulated IFN-γ transcripts and nitric oxide production by PBMCs (P < 0.05), and lower bursal lesion score in the experimental birds. In conclusion, poly I:C alone and its combination with Pam3CSK4 reduced the destruction of B cells as well as bursal damage with restoration of function of T cells and macrophages when used with a hot IBDV vaccine.